A regional inventory of rock glaciers and protalus ramparts in the central Italian Alps - SCOTTI, RICCARDO; BRARDINONI, FRANCESCO; FRATTINI, PAOLO; CROSTA, GIOVANNI; ALBERTI, STEFANO (Geomorphology, 2013)
Wepresent a regional inventory of rock glaciers (n=1514) and protalus ramparts (228) for the Lombardy region, central Italian Alps. To identify and classify the landformswe inspect three sequential air-orthophoto mosaics and a 2 m-DSM, and conduct confirmatory field work. The inventory forms an empirical basis to analyze: (i) the relative contribution of hillslope (i.e., talus slopes) and glacial (i.e., moraines) sediment stores to rock glacier sediment supply; (ii) linkages between the landforms inventoried and local topographic attributes; (iii) the spatial variability of periglacial activity in relation to a parsimonious set of environmental variables (i.e., elevation, precipitation, and lithology); and (iv) the effects of the Pleistocene–Holocene climatic transition on the distribution of intact and relict landforms. This analysis reveals that the elevation of rock glacier termini can vary over 200 m as a function of slope aspect. In turn, the distribution of rock glaciers among aspect categories is controlled by the structure of the valley network that promotes NWand SE exposures. Talus rock glaciers prevail numerically over the glacier-related typology, even though the latter population appears to have increased during the Holocene. Relict and intact rock glaciers have distinct spatial patterns in that the former display, on average, a 400-melevation drop and a less clustered distribution towards northern aspects, suggesting that they have developed in more “permafrost-prone” climatic conditions. Analyzing the study region through a 27.5 km-grid has been instrumental for showing that the rock glacier specific area and terminus elevation are: (i) positively correlatedwith terrain elevation; and (ii) negatively correlated with mean annual precipitation. As a consequence, in relation to Holocene generalized atmospheric temperature rise, intact rock glaciers have progressively disappeared fromthewetter and milder portions of the central Italian Alps. Analysis of rock glacier occurrence across litho-tectonic ...